community mental health service in Malaysia from the perspective of maqasid Shariah - Abdul Ghani Azmi, Ida Madieha; Ambaras Khan, Mushera Bibi; Safuan, Sahida (Universiti Putra Malaysia, 2021)
Introduction: The Mental Health Act 2001 provides a significant contribution to the treatment of mentally-ill patient. The emphasis of the previous law on isolation of psychiatric patients in the institutional settings has been replaced with encouragement of treatment in the community settings. Community Mental Health Service refers to a system of care in which the patient’s community is the primary care provider for people with mental illness. This treatment enables them to maintain relationships with others, as well as to retain jobs while receiving treatment. It leads to early intervention which facilitates rehabilitation and limit the stigma of treatment. Method: A doctrinal legal research to analyse the Community Mental Health Services enumerated in the Mental Health Act 2001 from the perspective of maqasid syariah. Result: The result from the study will provide insight to the authority to improve the existing service in line with maqasid shariah. Conclusion: Some recommendations are suggested as the way forward for the success of the Community Mental Health Programme in Malaysia